Pengaruh Pengalaman Magang, Minat Kerja, Soft Skill dan Motivasi Kerja terhadap Kesiapan Kerja Mahasiswa Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Riau - Vontinesa Amanda; Kurniawaty Fitri; Mida Aprilina Tarigan (CV. Ulil Albab Corp, 2024)
This study to determine the effect of internship experience, work interest, soft skills, and work motivation on work readiness of students majoring in Management Department, Faculty of Economics and Business, Riau University. The population in this study included all students majoring in Management class 2020, Faculties of Economics and Business, totaling 321 people with a sample of 178 people using the Slovin formula. This study used quantitative descriptive method with multiple linear regression analysis tools with the help of SPSS version 26. The results of this research showed that there is a positive and significant effect between internship experience on student work readiness, there is a positive and significant effect between work interest on student work readiness, there is a positive and significant influence between soft skills on student work readiness and there is a positive and significant influence between work motivation on student work readiness.